A novel chitosan alleviates pulp breakdown of harvested longan fruit by suppressing disassembly of cell wall polysaccharides. (1st August 2019) - Lin, Yifen; Lin, Yuzhao; Lin, Yixiong; Lin, Mengshi; Chen, Yihui; Wang, Hui; Lin, Hetong
Highlights: Chitosan treatment slowed down pulp breakdown development in harvested longan fruit. Chitosan reduced cell wall-degrading enzymes activities in harvested longan fruit. Chitosan helped preserve cell wall polysaccharides in pulp of harvested longan fruit. Chitosan suppressed cell wall disassembly in pulp of harvested longan fruit. Chitosan is a novel approach for keeping the quality of harvested longan fruit. Abstract: Longan pulp is an excellent source of polysaccharides and other nutrients that have many health benefits. However, longans is susceptible to pulp breakdown after harvest and loses its nutrition values. To solve this problem, this study aimed to study the effects of a novel chitosan, Kadozan, on pulp breakdown index, contents of pectin, cellulose and hemicelluloses, and activities of enzymes in longan pulp relating to disassembly of polysaccharides (XET, PE, PG, β -Gal, and cellulase). The data illustrated that, compared to the control longans, chitosan-treated longans contained higher amounts of CWM, CSP, ISP, cellulose and hemicelluloses, but exhibited lower pulp breakdown index, lower activities of cell wall-disassembling enzymes, and contained lower WSP amount. These results suggested that Kadozan with a dilution of 1:500 (VKadozan : VKadozan + Water ) could significantly decrease activities of disassembling-enzymes and depolymerization of polysaccharides in cell wall, and subsequently alleviate pulp breakdown and prolong storage-life of postharvest longans.